2016
DOI: 10.5056/jnm15172
|View full text |Cite
|
Sign up to set email alerts
|

Per Oral Endoscopic Myotomy in Children with Achalasia Cardia

Abstract: Background/AimsAchalasia cardia (AC) is a motility disorder, characterized by impaired lower esophageal sphincter relaxation and absence of esophageal peristalsis. AC is rare in children with unclear optimum management strategies. Per oral endoscopic myotomy (POEM) is a novel technique for management of achalasia with encouraging results in adult patients. The efficacy and safety of POEM is not known for pediatric AC. The aim of our study was to evaluate the safety and efficacy of POEM in children with achalas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 30 publications
0
25
0
4
Order By: Relevance
“…No complications or special technical difficulties were reported (68). The study by Nabi et al (69) reported a 100% efficacy in 15 children during a one year follow-up, including radiological evidence.…”
Section: Pediatric Patientsmentioning
confidence: 93%
“…No complications or special technical difficulties were reported (68). The study by Nabi et al (69) reported a 100% efficacy in 15 children during a one year follow-up, including radiological evidence.…”
Section: Pediatric Patientsmentioning
confidence: 93%
“…[15] Another study of 10 children included Eckhardt score, timed barium swallow, and high-resolution manometry one year after POEM and found significantly improved scores on these measures and complete symptom resolution. [23] The current lack of evidence supporting one treatment approach over another, combined with the rarity of achalasia in children, has led to wide variation in practice. [24] Well-designed multi-institutional studies are needed to improve treatment and prevent the adverse impact this disease has on a child's long-term quality of life.…”
Section: Esophageal Achalasiamentioning
confidence: 99%
“…Maselli et al [58] described the first case of achalasia treated with POEM in a pediatric patient. Following this, other cases have been reported with high clinical success rate [59,60]; however, the procedure should be performed in expert hands.…”
Section: Interventionmentioning
confidence: 87%